Schottky‐Contacted High‐Performance GaSb Nanowires Photodetectors Enabled by Lead‐Free All‐Inorganic Perovskites Decoration. Issue 16 (8th March 2022) - Liu, Dong; Liu, Fengjing; Liu, Yue; Pang, Zhiyong; Zhuang, Xinming; Yin, Yanxue; Dong, Shengpan; He, Longbing; Tan, Yang; Liao, Lei; Chen, Feng; Yang, Zai‐xing
Abstract: The surface Fermi level pinning effect promotes the formation of metal‐independent Ohmic contacts for the high‐speed GaSb nanowires (NWs) electronic devices, however, it limits next‐generation optoelectronic devices. In this work, lead‐free all‐inorganic perovskites with broad bandgaps and low work functions are adopted to decorate the surfaces of GaSb NWs, demonstrating the success in the construction of Schottky‐contacts by surface engineering. Benefiting from the expected Schottky barrier, the dark current is reduced to 2 pA, the I light / I dark ratio is improved to 10 3 and the response time is reduced by more than 15 times. Furthermore, a Schottky‐contacted parallel array GaSb NWs photodetector is also fabricated by the contact printing technology, showing a higher photocurrent and a low dark current of 15 pA, along with the good infrared photodetection ability for a concealed target. All results guide the construction of Schottky‐contacts by surface decorations for next‐generation high‐performance III–V NWs optoelectronics devices. Abstract : Schottky‐contacted high‐performance GaSb nanowires photodetectors are achieved by the surface decoration of lead‐free all‐inorganic perovskites. Benefiting from the expected Schottky barrier, the dark current is reduced to 2 pA, the I light / I dark ratio is improved to 10 3 and the response time is reduced by more than 15 times under the illumination of a 1550 nm laser.